Investor Reactions to the 2024 Presidential and Vice-Presidential Election Results According to Survey Institutions - Ni Wayan Budi Antari; Henny Triyana Hasibuan (Dinasti International Journal of Education Management And Social Science, 2025)
he 2024 Presidential and Vice-Presidential elections are crucial events that can impact fiscal and monetary policy, as well as the long-term investment climate. This study aims to test the extent to which the 2024 Presidential and Vice Presidential elections contain information that influences investors and market activity by analyzing the differences in abnormal returns, trading volume activity, and security return variability. The study was conducted on the LQ45 index, with 45 companies as samples. Observations were carried out over fifteen days. The analysis was carried out using the Wilcoxon Signed Rank Test. The results revealed differences in abnormal returns. In contrast, no differences were found in trading volume activity and security return variability before and after the event of the Presidential and Vice-Presidential elections.